(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fisheries sector is the fastest growing sector in Chhattisgarh state. Its contribution in the state economy shows a remarkable coverage. Chhattisgarh is endowed with abundant geographical resources and an apt climatic condition for production of fish. But fish being of highly perishable in nature need to be adequately processed. This paper primarily focuses on the” Prospects of Fish Processing Units in Chhattisgarh – An Overview” The objective to study the usefulness and response of other states towards this concept of fish processing industries and their impact on the economy of the State. The researcher found that processing of fish in organized way will be greater help to the fish farmers of state and will thus help in strengthening the financial status of people involved in this work. Immense scope is observed in fish processing industries in Chhattisgarh state.